Cyber Security Politics : Socio-Technological Transformations and Political Fragmentation. - Dunn Cavelty, Myriam; Wenger, Andreas (Milton : Taylor & Francis Group, 2022)
This book examines new and challenging political aspects of cyber security and presents it as an issue defined by socio-technological uncertainty and political fragmentation.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books